Pengembangan Kewirausahaan Melalui Peningkatan Kinerja Karyawan - Sukirman Sukirman (Jurnal Ekonomi dan Bisnis, 2014)
This study aimed to analyze the impact of the employee's performance towards the development of entrepreneurship. This study of employee performance involved variables of creativity, innovation and motivation. It analyzed the impact of creativity, innovation and motivation towards employee performance; it also analyzed the impact of creativity, innovation and motivation for the development of entrepreneurship and analyzed the impact of employee performance towards the development of entrepreneurship. The study focused on ‘Jenang Kudus’small scale businesses in Kudus Regency that covered 396 firms (Department of Industry and Trade, Kudus Regency, 2010) and focused on the small scale businesses under the auspices of the Department of Industry and Trade. The population in this study were all ‘Jenang Kudus’ Small Scale Business companies in Kudus Regency. The sample consisted of 86 companies. The purposive sample technique was used by selecting samples of the small scale businesses in Kudus Regency. Data were collected by using questionnaires and in-depth interviews and they were analyzed by using descriptive method. Employee performance was affected by the creativity, innovation, and motivation. Creativity had a significant and strong direct impact to the employee performance that could create improved performance for employees. Innovation also had a significant and strong direct impact towards employee performance; it is the yardstick in carrying out the day-to-day development of the company so that innovation was needed to improve the performance of employees in the interest of the company. Motivation didn’t have any strong and significant impact towards employee performance, it means that motivation is needed to create the performance of employees, so that employees will feel more comfortable and secure in carrying out their job. Both creativity and innovation had strong and significant impact towards the development of entrepreneurship, and on the other hand, motivation had no strong and significant impact towards the development of entrepreneurship.